Development of Teaching Materials to Support Merdeka Curriculum Learning on Salt Hydrolysis for Phase F Senior High School - Mardhiyatul Khairat; Mawardi; Okta Suryani; Reza Akmar (PT Inovasi Pratama Internasional, 2024)
This aims of this research is to develop teaching materials that incorporate multiple representations of chemistry concepts, especially on the salt hydrolysis topic, to support the Merdeka Curriculum and improve students' mental models in the F phase of high school. Educational Research Development (EDR) is the method chosen, using Plomp’s development model. The subject are three UNP chemistry lecturers, two chemistry teachers and nine SMAN 8 Padang students. The developed teaching material have been validated with a construct validity value of 0.89 which is classified as valid and. Then it has also been tested for practicality with a score of 96% from teachers and 94% from students, this shows that the development teaching materials are very practical, which indicates their ease of use and application in an educational environment. It concludes, that the developed teaching materials are for the topic of salt hydrolysis, which incorporate a comprehensive range of chemical representations proven to be valid and highly practical can effectively assist students in building mental models and improving their understanding of chemical concepts and support the goals of the Merdeka Curriculum in fostering deeper student understanding.